"They made me an offer I couldn't refuse!" Organizational commitment in a non-Western context. Issue 1 (3rd April 2018) - Bachkirov, Alexandre Anatolievich
Abstract : Purpose: The purpose of this paper is to explore the relationship between external monetary incentives (EMI) and affective commitment (AC), normative commitment (NC), and continuance commitment (CC). Design/methodology/approach: Data were obtained from a sample of 880 employees of different education and job levels, industries, sectors, and salary grades. Findings: An increase in EMI value is linked to a weakening of AC. In a non-Western context, specific employee characteristics – salary grade, educational level, industry type, and employment in the private vs public sector – are associated with different levels of CC. At the same time, employees at different job levels (top managers, middle managers, supervisor, and operative-level employees) are differently predisposed toward AC and NC. Job level emerged as a moderating variable between EMI and AC. Practical implications: Understanding of the ways in which EMI are related to organizational commitment will inform organizational decision makers about how to be more successful in retaining valuable employees. Originality/value: The study offers a systematic exploratory examination of the relationship between commitment components (AC, NC, and CC) and the amount of salary offered by an alternative employer.